Sectoral retinitis pigmentosa with pathological myopia - Shrinkhal; Pragati Garg; Aparajita Shukla (The Pan-American Journal of Ophthalmology)
Retinitis Pigmentosa (RP) is an inherited rod–cone disorder characterized by progressive degeneration of the retinal photoreceptors, manifesting as night blindness, visual field constriction. Sectoral RP is a rare variant of RP characterized by clinical and pathological involvement confined to one or two retinal quadrants. Pathological myopia with its complications can be associated with RP. This case highlights the importance of early recognition and management of these cases to prevent vision threatening complications.